DEVELOPING A ONE STOP SHOP MODEL FOR INTEGRATED LAND INFORMATION MANAGEMENT (Journal of Science and Technology, 2016)
In Ghana much attention has not been given to the development of land information system which will integrate the data on land ownership, land use and land value for all the land agen- cies under the land administration system to facilitate the processing of applications within the land delivery systems. This situation presents a lot of delays and inefficiencies in delivering land services to the investor and other potential clients of land sector agencies involved in the land administration practised in Ghana. This paper describes the development of a one stop shop model for integrating information on the attributes of a parcel and their accessibility. A cross sectional survey was conducted in six land sector agencies in Kumasi on data formats, standards and accessibility in provision of land delivery services to their clients. The results of the survey were then used to design a client server application based on a one stop shop concept to integrate the parcel attribute information. The client server application was designed with Microsoft SQL Server 2000, VB.Net 2005 and Microsoft Visio. A Land Management Key (LANMANK) program was finally developed with geodatabase capabilities for storing and displaying spatial data as well as other non-spatial data. LANMANK has a unique parcel identifier for land transactions such as land transfers, title registration, property rating, building and development permits proc- essing. Also, it allows the user to create back ups for the database and also restore the database at a later date.